Implementasi Asas Kepastian Hukum Dalam Pelaksanaan Perjanjian Kerja Waktu Tertentu (PKWT) Dalam Praktek Hubungan Industrial - Abdul Gofar Ar Rasyid; Ai Jauhari; Akhmad Cahrudin Carsa; I Ketut Margayasa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
A Fixed-Term Employment Agreement (PKWT) is a legal instrument used to regulate employment relationships for a specific period based on the needs of a particular type of work. However, in industrial relations practice in Indonesia, the implementation of PKWT often raises problems, particularly related to violations of formal requirements, unclear types of work, and the misuse of PKWT for permanent work. This condition indicates that the principle of legal certainty, as one of the fundamental principles in labor law, is often not optimally implemented. This study aims to analyze the implementation of the principle of legal certainty in the implementation of PKWT and examine various factors that cause disorder in its implementation. This research uses a normative juridical method with a statutory and conceptual approach. The results show that although regulations regarding fixed-term employment contracts (PKWT) are detailed in the Manpower Law and Government Regulation Number 35 of 2021, non-compliance by employers, minimal labor oversight, and imbalanced bargaining power result in the ineffective realization of the principle of legal certainty. This study recommends strengthening oversight, increasing employer compliance, and harmonizing regulations to ensure the implementation of the principle of legal certainty in PKWTs in accordance with their stated objectives.